Antecedents of consumers' Halal brand purchase intention: an integrated approach. Issue 4 (14th February 2018) - Ali, Afzaal; Xiaoling, Guo; Sherwani, Mehkar; Ali, Adnan
Abstract : Purpose: The purpose of this paper is to apply the concept of traditional branding constructs – brand image, brand satisfaction, brand trust and brand loyalty to an unexplored field of Halal products – Halal brand image, Halal brand satisfaction, Halal brand trust and Halal brand loyalty. In addition, this study seeks to elaborate the relationships among brand perceived quality, Halal brand image, Halal brand satisfaction, and Halal brand trust, Halal brand loyalty and consumer purchase intention. Design/methodology/approach: A theoretical model with hypothesised relationships is developed and tested with the help of structural equation modelling procedure in AMOS. This research used the questionnaire survey method to collect data from 347 consumers in Pakistan who had the experience of purchasing Halal milk brand. Findings: The empirical results suggest that perceived brand quality has a significant and positive influence on the Halal brand image, Halal brand satisfaction, Halal brand trust, Halal brand loyalty and purchase intention. Similarly, the Halal brand image, Halal brand satisfaction, Halal brand trust and Halal brand loyalty significantly influence consumer Halal brand purchase intention. Research limitations/implications: The Muslim population is growing in many parts of the world, including non-Muslim countries. Although this study's focus is limited to Pakistani Muslims, findings related to the effects of brand perceived quality, Halal brand image, Halal brand satisfaction, and Halal brand trust and Halal brand loyalty on intentions may not be equally valid for Muslim consumers in others Muslim and non-Muslim countries and for other types of products. Practical implications: The findings indicate that ignoring the important quality elements of a brand could be costly to marketers who failed to realise the importance of traditional brand attributes whilst embracing Halal brand marketing initiatives. In addition, Halal branding can allow the businesses to access to new markets, to enjoy more competitive advantages and to increase their profitability by selling at higher prices with higher profit margins. Originality/value: Although previous research has explored the relevant issues about brand image, brand satisfaction, brand trust and brand loyalty, none highlights these traditional constructs to an unexplored field of Halal products.